Development of Distraction Risk Index (DRI) Among the Intrastate Bus Driver in Kuala Lumpur, Malaysia - Annuar, Muhammad Nur; Sani, Jalil Azlis; Mohammad, Musli; Ngali, Mohd Zamani; Rohani, Munzilah; S.M. Ismail, S.M. Sabri; Ahmad Tajedi, Noor Aqilah (International Journal of Integrated Engineering, 2020)
Bus services is one of the main public transport chosen by the people all around the world especially in the big city such as Kuala Lumpur. However, the safety of the passenger of the bus services become main concern among the researchers due to increasing number of accidents among the bus services. Some researcher found that, the major factor of the accidents involving bus services was caused by the bus driver distraction. Therefore, the objective of this research is to develop the Distraction Risk Index (DRI) among the intrastate bus driver. This research will only focus on the intrastate bus driver in Kuala Lumpur. Survey which adapting the Hampton University Transportation Centre Bus Driver Distraction Survey was used and distributed to 215 intrastate bus drivers in Kuala Lumpur, Malaysia. It was found that there were four sources of distraction which classified as very high risk which were condition of the bus, traffic congestion, drivers’ welfare and drivers’ health. Findings of this research can be used as a platform for future improvement for the performance of the intrastate bus services. This research also can provide assistance to future researchers to design and provide solution to overcome sources of distraction.